Associations of individualized nursing care and quality oncology nursing care in patients diagnosed with cancer - Kousoulou, Maria; Suhonen, Riitta; Charalambous, Andreas (My University, 2019)
Purpose: To assess patients’ diagnosed with cancer perceptions on individualized nursing care and quality of oncology nursing care in Cyprus. Methods: This was a descriptive correlational research with 150 patients diagnosed with cancer and receiving treatment as in-patients at three different urban hospitals of Cyprus, based on predetermined inclusion and exclusion criteria. Data were collected with the Individualized Care Scale-ICS and the Quality Oncology Nursing Care Scale-QONCS. Statistical significance was set at the 0.05 level. Results: Data showed that a medium level of support of patients’ individuality was provided by nurses (ICS-A mean = 3.41, SD = 0.98) and a high level of realization of perceived individuality in the provided care. Quality of oncology nursing care was found high on three dimensions of care, i.e. being supported and confirmed, being respected and having a sense of belonging. A statistically significant positive correla-tion was observed between the two scales of ICS, i.e. ICS-A and ΙCS-B (r = 0.80), and four of the dimensions of QONCS, i.e. “Being supported and confirmed”, “Being cared for religiously and spiritually”, “Sense of Belonging” and “Being respected” and all the subscales, i.e. Clinical Situation (r = 0.45, 0.27, 0.41, 0.42), Personal life sit-uation (r = 0.30, 0.51, 0.44, 0.35) and Decision control (r = 0.35, 0.46, 0.35, 0.40). Conclusion: The correlations found between individualized care and quality of oncology nursing care, highlight the need to provide a more personalized nursing care as a means to achieve a high level of quality nursing care.
Keywords: Individualized care scale (ICS); Individualized nursing care; Patients diagnosed with cancer; Quality of oncology nursing care; Quality oncology nursing care scale (QONCS)